A magyar és a horvát nyelv szófaji rendszerei - Žagar Szentesi, Orsolya (Array, 1999)
Within the framework of the latest results of recent Hungarian researchers, the author presents, analyses and evaluates several systematizations of parts of speech in Hungarian and Croatian grammars which have been published in the last few decades.